Application of the Kenusantaraan Principle in the Formation of Customary Criminal Law in Regional Regulations: Penerapan Asas Kenusantaraan pada Konstruksi Hukum Pidana Adat dalam Peraturan Daerah - Alfath, Tahegga; Muhajjjalin , Muh Qoidul Qurril (Al-Jinayah : Jurnal Hukum Pidana Islam, 2025)
The content of the legislation requires reflection on the principle of archipelago, including in terms of the formation of customary criminal law in regional regulations. So that the problems discussed are the characteristics of customary crimes that need to be regulated in regional regulations, and the form of application of the principle of the archipelago. The research employs a legal approach, utilizing both the Statute Approach and the Conceptual Approach. The results obtained indicate that the characteristics of customary crimes that need to be regulated in regional regulations are based on Article 2 paragraph (2) of Law Number 1 of 2023 concerning the Criminal Code, namely Pancasila, the 1945 Constitution of the Republic of Indonesia, and Human Rights. The application of the principle of archipelago emphasizes the principle of a unitary state, considering the diversity that exists in each region. Regional governments must ensure that the regulations take into account applicable customary law, create tasks, and synchronize and harmonize with the rules above them. As a form of meaningful participation, the involvement of customary law figures in the formulation of regional regulations can ensure that customary law is accommodated appropriately.